Exploring Academic Writing Readiness in English as a Foreign Language: Progress in Measurement Instrument Design - Mujiono, Mujiono; Weganofa, Riza; Herawati, Siane (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
Exploring academic writing readiness is fundamental for EFL learners, underscoring the importance of refined measurement methods in global research. This study aims to assess the academic writing readiness of EFL learners and highlight the progress in the specifically designed measurement instrument. The study employed Confirmatory Factor Analysis (CFA) on 107 undergraduates in English studies to validate an academic instrument. Participants were selected for diverse experiences and underwent the survey in their usual classroom. CFA assessed factorial, convergent, and discriminant validity. Cronbach's alpha measured consistency, and data was analyzed using AMOS software. Adjustments were made when model discrepancies arose. The findings indicate that (1) the English Academic Writing Readiness scale dimensions encompass vocabulary, grammar, structure, formatting, and time management. (2) The structural equation model highlights five dimensions with respective factor loadings between 0.50 and 0.89. (3) The theoretical model aligns with observed data, supported by RMSEA, AGFI, TLI, and CFI. (4) The instrument reliably assesses five English Academic Writing Readiness dimensions. The findings imply refined pedagogical strategies for English academic writing instruction